A Bezoar Composed of Bilirubin Calcium, Calcium Carbonate, and Fatty Acid Calcium. (23rd May 2019) - Iwamuro, Masaya; Urata, Haruo; Hirata, Shoichiro; Ueki, Toru; Hanabata, Tetsuro; Takeda, Sho; Teraoka, Akira; Okada, Hiroyuki
Abstract : A 68-year-old Japanese man was diagnosed with bezoar in the stomach, which was endoscopically retrieved. The bezoar was composed of bilirubin calcium, calcium carbonate, and fatty acid calcium. Due to the presence of bilirubin calcium in the bezoar, we performed imaging studies of the bile duct; gallstones and common bile duct stones were identified. Although bezoar with components similar to bile is infrequently encountered, our findings suggest that a bezoar originating from bile should be considered among the differential diagnoses in patients without a recent consumption history of persimmons who demonstrate a mass in the digestive tract. This case highlights the importance of component analysis of gastric bezoars because its findings may alter the treatment plan.